Effect of Guided Inquiry on the Development of Critical Thinking in Science Learning in Junior High School Students: A Review - Calsabila Syasre Hidayat; Sri Wahyuni; Sri Rejeki Dwi Astuti; Siti Shofa Assyifa`ul Qulbi Barid (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Students in the 21st century are required to develop advanced thinking skills, especially critical thinking skills, which are essential for dealing with technological advances and scientific developments. Results from international studies indicate that Indonesian students, particularly at the junior high school level, still have relatively low critical thinking skills. This study aims to determine the extent to which guided inquiry approaches can strengthen critical thinking skills among junior high school students. The method used in this study was a Systematic Literature Review (SLR) that adopted the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. The articles analyzed are national and international publications from 2015 to 2025 that are relevant to the topics of Guided Inquiry and critical thinking skills. The synthesis results indicate that guided learning models are consistently effective at enhancing critical thinking skills, particularly in analysis, evaluation, and conclusion. This model requires students to be active in scientific investigation, engage in reflective thinking, and connect concepts to real-life contexts. The integration of the STEM approach, digital learning media, and local contexts further strengthens its effectiveness in shaping scientific and collaborative mindsets. The uniqueness of this study is evident in its comprehensive synthesis of the application of guided learning approaches in the 21st-century context, which emphasizes the integration of technology and contextual learning as a strategy for enhancing critical thinking. This study concludes that the Guided Inquiry Learning Model is an adaptive, innovative, and relevant learning model for strengthening critical thinking skills in the modern era, especially at the junior high school level.